Loss of Heterozygosity at the Glutathione Peroxidase 1 Locus Is Not an Early Event in Colon Carcinogenesis - Goldberg, Marci (SAGE Publications, 2011)
It has been previously shown that loss of heterozygosity (LOH) at the cytosolic glutathione peroxidase (GPx-1) locus is a common event in the development of several cancer types, including colorectal cancer. GPx-1 is an antioxidant selenium-containing protein, and polymorphisms within this gene have been shown to be associated with the increased risk of cancer. In order to assess whether this genetic change was an early or late event in colon cancer development, we investigated whether LOH at this site was occurring in colorectal adenomas, a premalignant lesion. Twenty-four pairs of DNA samples, obtained from both whole-blood and adenoma tissue from the same individuals, were genotyped at 2 positions in the GPx-1 gene: a codon 198 variation resulting in either a leucine or proline at the corresponding position in the peptide, or a variable number of alanine repeat codons corresponding to the amino terminus of the GPx-1 protein. No evidence of GPx-1 LOH was observed in the examined sample sets. These data indicate that the genetic loss at the GPx-1 locus may be a late event in colon carcinogenesis.